Language Game Design using vocabulary and dialogue in Baina Yadaik's book (Volume 1) To Understand New Vocabulary at Pondok Al-I'tikaf Al-Islamiyah Kubu Raya - Innayati, Nurul; Shodiq, Muh Fajar; Qosim, Muhammad Nanang (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The researcher wants to design some interesting and varied forms of language games to teach Arabic vocabulary and conversation using the Baina Yadaik book, the results of which will be used as media in teaching and learning Arabic because the methods used by the teacher are not diverse and are still monotonous, the author uses a qualitative approach in this study. The research methodology used by the researcher is descriptive-analytical research. The researcher designed several language games with the following steps: analyzing needs and problems, analyzing situations, planning general and specific objectives, designing language games, determining teaching methods, managing the contents of the designed games. These games consist of two types: the first is a game that uses vocabulary and the second uses conversation. The purpose of this study is to make it easier for students to understand the meaning of vocabulary and understand the conversation that will be delivered by the teacher concerned. In addition to these benefits, the use of this media is expected to make students feel interested and like the lesson and build curiosity. moreover, the lesson is very important and useful.